2019
DOI: 10.2174/1573399814666180724100749
|View full text |Cite
|
Sign up to set email alerts
|

Recent Updates on Glucokinase Activators and Glucokinase Regulatory Protein Disrupters for the Treatment of Type 2 Diabetes Mellitus

Abstract: The impairment of glucose metabolism leads to hyperglycemia and type-2 diabetes mellitus. Glucokinase enzyme is the key regulator of glucose homeostasis that catalyzes the conversion of glucose to glucose-6-phosphate in liver and pancreatic cells. In hepatocytes, GK controls the glucose uptake and glycogen synthesis. The action of liver GK is controlled by glucokinase regulatory protein (GKRP) partially. In fasting conditions the GKRP binds with GK and inactivate it from carbohydrate metabolism and serve as ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Therefore, a target-based computational approach was explored on compounds identified in the fractionated extract from our previous research for its anti-diabetic potential [16]. Our research focused on glucokinase (which has a vital role in glucose metabolism and as a rate limiting enzyme in the development of type 2 diabetes) as a molecular target for the identification of anti-diabetic components among the identified compounds [28]. Therefore, the results obtained from our research revealed four promising phytocompounds from E. africana (1057: pyrogallol; 5281672: myricetin; 5281692: robinetin; 5280443: apigenin) that possess some structural features and molecular interactions required for them to be considered for further experiments toward GK activation and glucose regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a target-based computational approach was explored on compounds identified in the fractionated extract from our previous research for its anti-diabetic potential [16]. Our research focused on glucokinase (which has a vital role in glucose metabolism and as a rate limiting enzyme in the development of type 2 diabetes) as a molecular target for the identification of anti-diabetic components among the identified compounds [28]. Therefore, the results obtained from our research revealed four promising phytocompounds from E. africana (1057: pyrogallol; 5281672: myricetin; 5281692: robinetin; 5280443: apigenin) that possess some structural features and molecular interactions required for them to be considered for further experiments toward GK activation and glucose regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Glucokinase (GK) is an essential enzyme in glucose metabolism and a potential therapeutic target in type 2 diabetes [27]. The glucokinase enzyme is a principal regulator of glucose homeostasis within the liver and pancreatic cells [28,29]. Therefore, this enzyme suffices as an ideal drug target, especially in type 2 diabetes, because its activation reduces the blood sugar level [29].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that common variants in the GCKR gene are associated with increased blood triglycerides [37,38], lower fasting glucose [38], and NAFLD [39]. The glucokinase regulator protein, which binds with glucokinase and inactivates it from carbohydrate metabolism, is able to serve as a new treatment target for T2DM [40]. Signi cantly lower levels of GCKR mRNA in the SHS individuals in this study indicate that disorders of glucose metabolism might play an important role in the pathophysiology of SHS.…”
Section: Discussionmentioning
confidence: 99%
“…Glucokinase (GK) is an essential enzyme in glucose metabolism and potential therapeutic targets in type 2 diabetes (Mekhilef et al, 2012). The Glucokinase enzyme is a principal regulator of glucose homeostasis within the liver and pancreatic cells (Kaushik & Kaushik, 2019;Wang et al, 2021). Therefore, this enzyme su ces as an ideal drug target, especially in type 2 diabetes, because its activation reduces blood sugar level (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%